Macroeconomic Factors and Stock Market Returns: A Study in Indian Context - Sharad Nath Bhattacharya; J. K. Dasa (Journal of Accounting, Business and Management (JABM), 2014)
This paper analyses returns on four equity indices of the Indian capital market in the period from July 2000 to June 2010. Methodology involves sample adequacy tests, factor analysis followed by Cochrane and Orcutt regression analysis. Findings suggests that three statistical factors from linear combinations of several macroeconomic indicators explain significant cross sectional variation in return. These three factors may be proxy for money market factor, foreign involvement factor and domestic macroeconomic factor. The results suggest, consistent with other previous studies, that stock returns are a function of a number of previously identified set of macroeconomic variables. These macroeconomic variables could be represented by a number of estimated macro factors.